Возможности капилляроскопии в клинической практике - Ковалева, А. А.; Аврунін, О. Г. (ХНУРЕ, 2019)
A pressing issue of modern medicine is the search for new diagnostic methods, allowing to identify the smallest changes at the preclinical stage. Biomicroscopic methods for studying capillary blood flow have traditionally been used to study microcirculation. One of the most relevant and promising methods is capillaroscopy. Therefore, in the work was considered a mathematical model that describes the metabolic processes in the human body. It allows to analyze the dependence of the volumetric filtration rate on various parameters. Using the results, it is possible to quantify the intensity of metabolic processes in health and disease, and draw conclusions about the most likely causes of microcirculation pathologies. In this regard, the study of the parameters of capillaries allows us to judge not only the functioning of central hemodynamics, but also to determine the diagnostic and prognostic criteria for the pathology of various organs.
Keywords: капиляроскопия; метод диагностики